Czas, Pamięć, Śmierć - Vladimira Nabokova triada estetyczno-filozoficzna = Time, Memory, Death - Vladimir Nabokov's aesthetical-philosophical triade - Kotin, Andrej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article focuses on three decisive aspects of Vladimir Nabokov's thoughts and works: memory, time and death. The introductory section gives a general sketch of the temporal problematics connected with literary art; subsequently, ones delves into concrete examples from the novels, essays and statements of Nabokov so as to demonstrate the very specific aesthetic/philosophic approach to the nature of time and consciousness which can be observed in the selected texts.
Keywords: Nabokov, Vladimir (1899-1977); temporalność w literaturze; pamięć; Śmierć; przemijanie; świadomość; temporality in literature; memory; vanishing; consciousness; death